Effect of Phenolic Compounds from Almond Skins Obtained by Water Extraction on Pork Patty Shelf Life - Marisa Timón; Ana Isabel Andrés; Ludovico Sorrentino; Vladimiro Cardenia; María Jesús Petrón (MDPI AG, 2022)
The extraction of phenols from almond skin using water has not been applied before. The purpose of this study was to obtain aqueous extracts from almond skin to be added to pork patties to prolong their shelf life. Four different varieties of almonds were studied and aqueous extracts were obtained. The antioxidant capacity and composition of phenol compounds of the extracts were determined. Results showed that the use of water produces extracts with phenol compounds and antioxidant capacity, with the Antoñeta variety presenting the best performance in terms of antioxidant behavior. The most abundant phenolic compounds identified were isorhamentin-3-O-rutinoside, catechin and protocatechuic acid, all of them had a hydrophilic character due to the -OH groups in their molecules. The effect of almond skin extracts (ALMOND) on the shelf life of pork patties was compared with the effects of a control without extract (CONTROL NEG) and a control with sodium ascorbate (CONTROL POS). Throughout storage, values of pH, weight loss, headspace composition, color, TBARs and psychrotrophic aerobic bacteria were studied. CONTROL POS samples showed the lowest lipid oxidation values in comparison to CONTROL NEG or ALMOND extract samples.